2020
DOI: 10.1038/s41598-020-67482-9
|View full text |Cite
|
Sign up to set email alerts
|

miRNA–mRNA network regulation in the skeletal muscle fiber phenotype of chickens revealed by integrated analysis of miRNAome and transcriptome

Abstract: Skeletal muscle fibers are primarily categorized into oxidative and glycolytic fibers, and the ratios of different myofiber types are important factors in determining livestock meat quality. However, the molecular mechanism for determining muscle fiber types in chickens was hardly understood. In this study, we used RNA sequencing to systematically compare mRNA and microRNA transcriptomes of the oxidative muscle sartorius (SART) and glycolytic muscle pectoralis major (PMM) of Chinese Qingyuan partridge chickens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 57 publications
3
23
0
Order By: Relevance
“…[29] reported the function of miRNA-122 in adipose tissue by opposite expression trend to PPARG. Intramuscular fat deposition also reported a relationship with miRNA function showed that the expressed miRNAs and there were involved in energy metabolism, glycerophospholipid metabolism, fatty acid elongation, and degradation pathways, insulin signaling, and PPAR function via miRNA-499-5p/SOX6 and miRNAs-196-5p/CALM1 [30,31]. This adipogenic regulation was described by [30] to demonstrate that intramuscular adipocyte differentiation was controlled via miRNA-140-5p promote targeting retinoid X receptor gamma, which co-activated function with PPAR and lead to mRNA levels of the PPARG and A-FABP increased with adipocyte differentiation.…”
Section: Ppars Transcription Factors Regulating Cellular Lipid Metabomentioning
confidence: 95%
“…[29] reported the function of miRNA-122 in adipose tissue by opposite expression trend to PPARG. Intramuscular fat deposition also reported a relationship with miRNA function showed that the expressed miRNAs and there were involved in energy metabolism, glycerophospholipid metabolism, fatty acid elongation, and degradation pathways, insulin signaling, and PPAR function via miRNA-499-5p/SOX6 and miRNAs-196-5p/CALM1 [30,31]. This adipogenic regulation was described by [30] to demonstrate that intramuscular adipocyte differentiation was controlled via miRNA-140-5p promote targeting retinoid X receptor gamma, which co-activated function with PPAR and lead to mRNA levels of the PPARG and A-FABP increased with adipocyte differentiation.…”
Section: Ppars Transcription Factors Regulating Cellular Lipid Metabomentioning
confidence: 95%
“…Liu et al (2020) systematically compared the mRNA and miRNA transcriptomes of oxidative muscle sartorius (SART) and glycolytic muscle pectoralis major (PMM) in Chinese Qingyuan partridge chickens using RNA sequencing. They found that MiR-499-5p and MiR-196-5p were most abundant and upregulated in SART and demonstrated that MiR-499-5p targets SOX6 (a repressor of slow muscle-specific gene expression), whereas MiR-196-5p targets CALM1 (a key component of the cGMP-PKG and calcium signaling pathways), both together regulating slow muscle fiber formation [ 1 ].…”
Section: Mirna Modulates Skeletal Muscle In Domestic Chickenmentioning
confidence: 99%
“…Chicken is a high-quality animal protein and is the most widely consumed meat product in the world ( , accessed on 14 May 2022). Meat is a major end product of poultry production, and the skeletal muscle, which makes up most of the meat and is the most valuable part of chicken meat products, is strongly linked to meat production and quality [ 1 ]. Skeletal muscle formation is based on the process of myogenesis, which is a multi-step process [ 2 ], and in domestic chicken is separated into two stages: embryonic and postnatal.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies have identified that the different types of muscle fibers to influence many meat quality traits such as the water-holding capacity (WHC), tenderness, color, juiciness, and flavor ( 15 ). Liu et al ( 16 ) demonstrated CaN/NFAT as an important signaling pathway, regulating the transformation of the chicken muscle fiber types. Zhu et al ( 17 ) found MYH6 and Ca 2+ signaling pathways to regulate the muscle fiber types of skeletal muscle in large white pigs.…”
Section: Introductionmentioning
confidence: 99%